Generalized 𝑆(𝐶,𝐴,𝐵)-Pairs for Uncertain Linear Infinite-Dimensional Systems - Naohisa Otsuka; Haruo Hinata (Journal of Applied Mathematics)
We introduce the concept of generalized 𝑆(𝐶,𝐴,𝐵)-pairs which is related to generalized 𝑆(𝐴,𝐵)-invariant subspaces and generalized 𝑆(𝐶,𝐴)-invariant subspaces for infinite-dimensional systems. As an application the parameter-insensitive disturbance-rejection problem with dynamic compensator is formulated and its solvability conditions are presented. Further, an illustrative example is also examined.